Evaluation Of Zonation System Implementation For Passengers And Vehicles In Marisa Flighting Port, Pohuwato District, Gorontalo Province, 2020 - Purboyo Purboyo; Hartanto Hartanto; Muhammad Fadjri (IWJ : Inland Waterways Journal, 2021)
Marisa Ferry Terminal is a port that serves the Marisa - Dolong - Supply - Ampana route. The existence of the Marisa Ferry Port has a very important role in supporting economic activity and equitable development in Pohuwato Regency. However, at this time many people and unauthorizedvehicles can easily enter the port area, causing the port to become less regulated, such as traders who sell their merchandise at port area, delivery / pick-up enters the port dock area. This is due tothe absence of a zoning system in accordance with the Regulation of the Minister of Transportation Number: 29 of 2016 concerning the Sterilization of Ferry Ports. So that in the activity of getting on and off of passengers and loading and unloading vehicles, there are several obstacles, among others, the irregularity of the traffic flow pattern, the absence of zoning in the port which causes unauthorized people to enter restricted areas. This research aims to; 1) To Know Sterilization Passengers and Vehicles at the Ferry Port. 2) To analyze the existing conditions of passenger and vehicle sterilization at the Marisa Ferry Terminal, Pohuwato Regency, Gorontalo Province in 2020. 3) And to evaluate the sterilization of passengers and vehicles and any supporting facilities needed. The research methodology used is direct observation in the field (field research) with measurement studies and literature (literature). Then to analyze this based on the Decree of the Director General of Land Transportation Number SK, 242 / HK.104 / DRJD / 2010 concerning Technical Guidelines for Ferry Traffic Management and PM Number 29 of 2016 regarding ferry port sterilization. The analysis used is the zone system analysis, analysis of vehicle and passenger traffic patterns and the equipment needed to supportthe zone system. As for the results of this study are 1) That the sterilization of passengers and vehicles is a zone arrangement system at the crossing port from the accumulation of passengers and vehicles. 2) Whereas the existing conditions of the Marisa Ferry Port, pohuwato district, Gorontalo province are not in accordance with the Minister of Transportation Regulation Number29 of 2016 concerning the Sterilization of Ferry Ports. 3) And that the evaluation in this researchstates that there are no supporting facilities such as weigh bridges and portals at the Marisa Ferry Terminal which results in an accumulation of the number of passengers and vehicles while operating.